Perioperative antibiotic prophylaxis for stone therapy. Issue 2 (March 2019) - Schnabel, Marco J.; Wagenlehner, Florian M.E.; Schneidewind, Laila
Abstract : Purpose of review: To give an overview about state-of-the-art antibiotic prophylaxis in urolithasis therapy and focus on recent publications in this field. Recent findings: The number of high-quality publications within the recent time is limited. Preoperative inflammatory blood parameters like C-reactive protein and erythrocyte-sedimentation rate might help in prediction of postoperative systemic inflammatory response syndrome (SIRS) after percutaneous nephrolithotomy (PCNL). White blood cell count is nonpredictive for urinary tract infection (UTI) in patients with acute renal colic. In patients with low risk for infectious complications, antibiotic prophylaxis during shock-wave lithotripsy (SWL) is unnecessary and single-dose antibiotics are comparably effective as prolonged antibiotic usage during PCNL and ureterorenoscopy (URS). Summary: Current findings support the American Urological Association (AUA) and European Association of Urology (EAU) guideline recommendations for a risk-adapted minimal antibiotic usage. Single-dose antibiotic prophylaxis is sufficient for low-risk PCNL and URS. For SWL no antibiotic prophylaxis is needed.